Plasticity of Locomotor Activity Permits Energy Homeostasis During Reproduction in a Female Sea Cucumber - Ru, Xiaoshang; Zhang, Libin; Yang, Hongsheng (Frontiers in Marine Science, 2021)
Behavioral plasticity in animals allows for moment-by-moment behavioral adjustments to biotic and abiotic uncertainties in the environment. For most aquatic animals, reproduction involves gonadal development and other physiological changes, causing increasing demands in nutrients and energy for females. The aim of this report was to determine how the female sea cucumber, Apostichopus japonicus, accommodates increasing energy demands during reproduction by adopting a behavioral energy conservation strategy. Dynamic changes in feeding activity, total body mass, locomotor activity, energetic condition, and metabolic performance of the females were measured from the non-breeding stage up to the mature stage. Routine metabolic rate analysis showed that reproduction caused a significant increase in energy demands in the adult. However, reproduction also suppressed the appetite of adults resulting in decreased energy intake. Interestingly, combining time-lapse camera and behavioral analysis software, the results showed that sea cucumbers down-regulated their locomotor activities in order to conserve energy effectively. Energy budget analysis and unchanged cortisol level revealed that the reduction in motility offset the increased energy demand for reproduction while helping to maintain energy homeostasis in the maternal body. Altogether, our study suggests that plasticity in the locomotor behavior allows sea cucumbers to cope with the high energy demands of reproduction.